Acoustic Emission for Structural Monitoring of Historical Masonry: An In-Field Application - Luciana Di Gennaro; Giovanni Loreto; Giorgio Frunzio; Gianvittorio Rizzano; Claudio Guarnaccia (Applied Sciences)
Acoustic Emission is a non-invasive technique with potential applications in Structural Health Monitoring (SHM), particularly for assessing historic masonry structures. However, its use in this field is complex due to the heterogeneous nature of masonry, where variations in density, mortar joints, and internal discontinuities influence signal propagation, leading to attenuation and distortion that complicate damage detection and localization. Nonetheless, AE can offer qualitative insights into damage initiation and progression, serving as a complementary approach to traditional monitoring methods. This study explores the feasibility of AE through an in-field test conducted on the historic Santa Maria delle Grazie complex, assessing its ability to capture qualitative indicators of structural behaviour. By integrating AE results with data from conventional monitoring instruments, a comprehensive interpretation of the load test outcomes was developed despite the challenges posed by the irregularities of ancient masonry. The findings contribute to the ongoing evaluation of AE as a diagnostic tool and highlight its potential role in heritage conservation strategies.